Editorial - Oorschot, Frederike van; Reichel, Hanna (Cursor_, 2022)
In the digital age, all aspects and subsystems of life are undergoing transformations, sometimes radically and other times subtly. What, if anything, can theology as a discipline contribute to the analysis, conceptualization and assessment of the emergent logics of "the digital"? And how are theological concepts and topics themselves transformed by "the digital"? A group of German, South African, and U.S. theologians explored these pressing questions at a virtual workshop in 2021, relating theological issues that are crucial to the life of the church and Christian ethics.